Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.